Nationwide estimations of tracheal stenosis due to tracheostomies. (19th December 2018) - Johnson, Romaine F.; Saadeh, Charles
Abstract : Objectives: Tracheal stenosis is a recognized complication of tracheostomy. Yet, the incidence and demographics of tracheal stenosis due to tracheostomies have infrequently been studied. Methods: We performed a cross‐sectional analysis of U.S. emergency department (ED) visits, hospital discharges, and readmissions using the 2013 National Emergency Department Sample, 2013 National Inpatient Sample, and 2013 Nationwide Readmission Database for patients with tracheal stenosis due to tracheostomies. Also, we queried the readmission database for new tracheostomy patients who were readmitted within the same calendar year with tracheal stenosis due to the tracheostomy tube. Results: There were an estimated 6, 156 ED visits; 4, 920 hospital discharges; and 2, 316 readmissions for tracheal stenosis due to tracheostomies in 2013. These cases represented 28% of all tracheostomy‐related complications. Of the 103, 484 patients who underwent tracheostomy in 2013, 739 (1.05%) patients were readmitted within the calendar year with tracheal stenosis due to the tracheostomy tube. These stenosis patients' average age was 55 years old. Forty‐five percent of the patients were female and 60% were white. The mortality rate was 7.9%. The demographic risk of stenosis mirrored the risk of tracheostomy: increasing age, male gender, and black ethnicity. Conclusion: Tracheal stenosis due to tracheostomy was uncommon, accounting for 1% of readmissions after tracheostomies, although it represented 28% of tracheostomy‐related complications and had a high mortality rate. The risk of stenosis reflected the overall tracheostomy population without apparent age, gender, or racial predilections. Level of Evidence: NA Laryngoscope, 129:1623–1626, 2019